The Role of Corona Era to Open Opportunity Internationalize, Walless And Equity or Equality School (Kindergarten Until University, Special Education, Formal and Informal) in The World As Suggestion Policy - Hidayanto, Nova Eko (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Before Covid-19 Pandemic,generally to builtschools (kindergarten until university, formal and informal)must be there wall or building to made class for learning process (face to face) teacher and students and these was vary, therewere small and big, both of building and quality or level.Since Covid-19 Pandemic happen big economic crisis in the world, of course werelost of job, bankruptcybecause close of companies,lock downand must be using of elearning or online learning in all schools in the worldto avoid spreaded of this desease. Because of that,elearning could be used for many benefit opportunity, among them are internationalized, walless and equity concrete or hard schools. Futhermore had found free, best, simplest elearning software (as simple as blog made, not using programing language) in the Moodlecloud.com, Google Classroom and Zoom Meeting Online.Thiswas a literature reviewknown as library research.The search strategywasdocumentationfrom articles and books,etc. This was conducted from April to July 2021 that included electronic database: Science Direct and Google Scholar. The other,had found Bank transfer for along time ago and internet as a key for all utilization so that can be used student’s registerwith google form.